What Drives People to Use Grocery Apps? The Moderating & Mediating Role of Customer Involvement and Trust - Chakraborty, Debarun; Altekar, Shrirang (Indian Journal of Marketing, 2021)
Grocery apps are gaining popularity day by day, and their benefits were well acknowledged by the consumers, especially during the pandemic or during the lockdown. Despite the growing awareness of grocery applications, little is known about the consumer values that influence the intention to buy. Grocery apps must boost client engagement by offering superior value propositions to overcome this barrier. The current research suggested the consumption value theory to fill this gap, which will better explain consumer behavior toward grocery apps. The proposed model was tested using data from 436 users of grocery apps. The data revealed that all the consumption values positively and significantly influenced the intention to use grocery apps. The moderating effect of customer involvement on intention to use was also verified, as was the mediating role of trust. The outcomes of the study added to our understanding of consumer behavior and practice.